1978
DOI: 10.1093/ptj/58.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Study of Three Parts of the Gluteus Medius Muscle During Functional Activities

Abstract: This study was undertaken to determine the onset, duration, and degree of electromyographic activity in the anterior, middle, and posterior segments of the gluteus medius muscle during functional activities. Fine wire electrodes were inserted into each muscle segment. After a triaxial hip electrogoniometer was applied, each of the 10 subjects performed the activities of walking, crawling, stair ascending and descending, shoetying, sitting, and single limb-standing with forward learning. Raw electromyographic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 0 publications
8
49
0
1
Order By: Relevance
“…However, these results were derived from subjects with numerous musculoskeletal disorders 2,15,[25][26][27] . Therefore, this provides further evidence that rehabilitation programs aimed at increasing the strength and activation of hip muscles, such as the GM, are effective at reducing pain and disability and improving lower limb kinematics and athletic performance 2,5,27) . The results of the present study suggest that the proper exercise method for GM-strengthening exercises for the anterior fiber is WP-ABD, and that for the posterior is WS-ABD.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, these results were derived from subjects with numerous musculoskeletal disorders 2,15,[25][26][27] . Therefore, this provides further evidence that rehabilitation programs aimed at increasing the strength and activation of hip muscles, such as the GM, are effective at reducing pain and disability and improving lower limb kinematics and athletic performance 2,5,27) . The results of the present study suggest that the proper exercise method for GM-strengthening exercises for the anterior fiber is WP-ABD, and that for the posterior is WS-ABD.…”
Section: Discussionmentioning
confidence: 81%
“…A number of studies have investigated both the whole GM and its muscle fiber subdivisions [21][22][23] . We also investigated the GM subdivisions, as suggested by previous anatomical studies 5,7,24) . Our present results suggest that the GM subdivisions were activated in isolation and not simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,28,31 Anatomically, these muscles provide lateral stability of the hip joint and pelvis, as they help to control the contralateral pelvic position during unilateral stance in the frontal plane. 27 A 1978 study 49 reported segmental differences in GMed electromyography (EMG) muscle activity. More recently, cadaveric and segments of the GMin are structurally and functionally suited to provide femoroacetabular stability.…”
mentioning
confidence: 99%
“…However, different muscles respond in different ways depending on the loading; during gait, the gluteus medius muscle fiber activation fluctuates (i.e. anterior fibers may be active when the posterior ones are not and vice versa) (Soderberg et al, 1978).…”
Section: Physiologic Loading Conditions In Fe Codesmentioning
confidence: 99%